The Relationship Between Murabahah And Musyarakah Financing And Profitability: A Case Study Of BMT Hasanah - Syamsul Arifin; Alifiani Hidayatus Sholekhah; Rokhmah Nur Jannah; Devangga Putra Adhitya Pratama; Kurniawati Kurniawati; Mahmud Ismail (INVENTORY: JURNAL AKUNTANSI, 2025)
This study aims to describe the effect of murabahah and musyarakah mutanaqishah financing on the effectiveness of BMT Hasanah's profit earning during the covid-19 pandemic. This research method uses quantitative methods, data collection techniques used are documentation techniques. The data analysis technique used is multiple linear regression technique. The results of this study based on a partial test showed that murabahah financing had no effect on BMT Hasanah profits, while musyarakah mutanaqishah financing had a negative effect on BMT Hasanah profits. Then the results of the simultaneous test show that murabahah and musyarakah mutanaqishah financing have a simultaneous positive effect on BMT Hasanah's profit.Simultaneously both have an effect on ROA. Shows the results of the R square value of 0.984.